Walkability assessment for university campuses in the MENA region. Case of Applied Science Private University (ASU), Amman, Jordan - Majida Yakhlef; Deyala Tarawneh (Urban, Planning and Transport Research)
This study investigates the quality of pedestrian environments’ walkability at university campuses in MENA contexts. The Applied Science Private University (ASU) in Amman, Jordan, was employed as a study case; a total of (19) street segments were analysed, and a sample total of (57) campus users were considered. The study adopted mixed-methods including spatial mapping, photographic documentation, a tailored survey, and, an adaptation of the CDC audit tool which was developed for the study context – considering shade and terrain as two unique factors. The results were analysed using statistical tests, including the Cronbach alpha test, mean and standard deviation analysis, T-test, One-way ANOVA, and Bonferroni post hoc test. The results yielded that the campus has medium walking attractiveness. The average score for walkability suggests that it is considered a setting with intermediate risk for pedestrians and generally provides a pleasant and visually attractive environment. The study’s findings indicate that pedestrian facilities scored higher than vehicle-pedestrian roads. The mean value for both variables suggests that the presence of campus roads impacts the walkability of the environment. Overall, the study concludes that ASU has an opportunity to develop a more walkable campus by utilizing available landscapes to improve environmental quality and resources.